A High‐grade Sarcoma Arising in a Patient With Recurrent Benign Giant Cell Tumor of the Proximal Tibia While Receiving Treatment With Denosumab. Issue 9 (September 2015) - Aponte‐Tinao, Luis A.; Piuzzi, Nicolas S.; Roitman, Pablo; Farfalli, German L.
Abstract: Background: A giant cell tumor of bone is a primary benign but locally aggressive neoplasm. Malignant transformation in a histologically typical giant cell tumor of bone, without radiotherapy exposure, is an uncommon event, occurring in less than 1% of giant cell tumors of bone. Although surgery is the standard initial treatment, denosumab, a monoclonal antibody drug that inhibits receptor activator of nuclear factor‐κB ligand (RANKL), has shown considerable activity regarding disease and control of symptoms in patients with recurrence, unresectable, and metastatic giant cell tumors of bone. Case Description: We report the case of a 20‐year‐old woman with a recurrent benign, giant cell tumor of bone, who had a bone sarcoma develop while receiving denosumab treatment. Literature Review: To our knowledge, there have been no reports of infection or malignancy with low‐dose denosumab administration for osteoporosis. However, while there are relatively few reported side effects, the safety of denosumab and adverse events seen with higher doses, as used in treatment of giant cell tumors of bone are not well defined. Clinical Relevance: Denosumab has become a valuable adjunct for treatment of recurrent or unresectable giant cell tumor of bone. It is not clear if our patient's malignant transformation of a giant cell tumor of bone while receiving denosumab treatment was caused by denosumab, but it is important to be aware of the possibility if more cases occur. Future studies should focus on the safety of high‐dose denosumab administration in patients with a benign unresectable giant cell tumor of bone.